Evaluación de la viabilidad técnico-financiera del uso de sulfato de aluminio líquido o hidroxicloruro de aluminio (PAC) como reactivo sustituto del sulfato de aluminio granular en el subproceso de coagulación y floculación de la PTAP El Dorado (2018)
This work focuses on the coagulation and flocculation subprocess, which is a fundamental part for the elimination of suspended solids and dissolved colloids in the water, and occurs from the Parshall gutter, where the coagulant substance is added, up to the flocculating trains, where this stage ends. Because granular aluminum sulfate is currently used as a coagulant, problems have been experienced with the reagent dosing system, generating monetary losses of approximately 15.7 million pesos per year and increasing the amount of work done in the process, for this reason is proposed the change of aluminum sulphate granular to liquid, and also the aluminum hydroxychloride is suggested as a substitute, which can help in the subprocess of alkalinization Carrying out the experimental development and financial analysis of coagulants, it is found a great advantage in the use of aluminum hydroxychloride as a coagulant in the process of water purification.